Broadband strategies handbook [ - Kelly, Tim [ (Tim John Charles)]; Rossotto, Carlo Maria , 1970- (World Bank Publications, 2012)
"The Broadband Strategies Handbook is a guide for policymakers, regulators, and other relevant stakeholders as they address issues related to broadband development"-- provided by publisher